(untitled) (Minerva, 2019)
First, we study the different kinds of marriage we can find in Roman Law; then, the survival and changes of marriage rituals until Middle Ages. We analyse rituals from the day before wedding to the bride’s driving into her new home, the first night and the day after wedding.